2001
DOI: 10.1023/a:1017524022270
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The R-band isophotal map of the Sa galaxy NGC 4698 shows that the inner region of the bulge is elongated perpendicularly to the major axis of the disc. At the same time a central stellar velocity gradient is found along the minor axis of the disc. The same properties have also been recognized in the Sa galaxy NGC 4672. This remarkable geometric and kinematic decoupling is a direct indication that a second event occurred in the history of these galaxies suggesting that acquisition phenomena could play a primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…suggests that ESO 603-G21 could be an unusual late-type spiral galaxy with a kinematically-decoupled extended "bulge". Therefore, it may be similar in some respects to NGC 4672 and NGC 4698, which are early-type disk galaxies with geometric and kinematical orthogonal decoupling between the bulge and disk (Bertola et al 1999;Sarzi et al 2000), or to NGC 2748, which is a late-type spiral galaxy with possible ongoing accretion of a dwarf companion onto the central region of the galaxy (Hagen-Thorn et al 1996). The bulge-like feature of ESO 603-G21 can be a "true" polar ring that is formed during almost perpendicular accretion of an early-type companion onto central region of a pre-existing disk galaxy.…”
Section: Discussionmentioning
confidence: 95%
“…suggests that ESO 603-G21 could be an unusual late-type spiral galaxy with a kinematically-decoupled extended "bulge". Therefore, it may be similar in some respects to NGC 4672 and NGC 4698, which are early-type disk galaxies with geometric and kinematical orthogonal decoupling between the bulge and disk (Bertola et al 1999;Sarzi et al 2000), or to NGC 2748, which is a late-type spiral galaxy with possible ongoing accretion of a dwarf companion onto the central region of the galaxy (Hagen-Thorn et al 1996). The bulge-like feature of ESO 603-G21 can be a "true" polar ring that is formed during almost perpendicular accretion of an early-type companion onto central region of a pre-existing disk galaxy.…”
Section: Discussionmentioning
confidence: 95%
“…This peculiarity makes ESO 603-G26 similar to a late-type spiral galaxy with a kinematically-decoupled extended bulge (e.g. NGC 4672 and NGC 4698, see Bertola et al 1999 andSarzi et al 2000) rather than a polar ring galaxy, as also suggested by Reshetnikov et al (2002). As we will show in Paper II, the central component of ESO 603-G26 has colors, age and light distribution properties quite similar to those of the host galaxy in the other PRGs of our sample.…”
Section: Description and Discussion Of Each Galaxymentioning
confidence: 99%
“…In spite of gravitational perturbations, some stellar and gaseous components with a misaligned or even opposite angular momentum with respect to its core, conserve some dynamical memory of processes which drive galaxy formation and evolution. In normal galaxies, kinematically-decoupled components ranging from the counter-rotating-decoupled disks of ionized gas are observed in a large fraction of S0 galaxies (Bertola et al 1992;Kuijken et al 1996;Plana & Boulesteix 1996), and orthogonally-rotating stellar cores are found in Sa spirals (Bertola et al 1999;Sarzi et al 2000). These characteristics are usually hidden from preliminary morphological inspection and are serendipitously discovered only by detailed kinematics studies (see Bertola & Corsini 1998 as review).…”
Section: Kinematics Of Hrg 54103mentioning
confidence: 99%